Von der Nützlichkeit des Unnützen: Über den Sinn der Poesie im fremdsprachlichen Unterricht - Irena Samide (Vestnik za Tuje Jezike)
The article discusses the role of literature in foreign language teaching, with a specific focus on the genre of poetry. It unequivocally answers the central question of whether incorporating literary texts into foreign language classrooms is meaningful and beneficial. The article challenges the widespread notion that students must have an advanced level of language proficiency to engage with literary texts. Through three very different examples of authentic poetry, it demonstrates how literary texts can be seamlessly integrated into foreign language teaching and which competencies can be developed through poetry. The analysis of the poem Der Apfel (The Apple) by Reinhard Döhl illustrates that literary texts can be meaningfully utilized from the very first lessons of language learning. Furthermore, the article focuses on one of the most prominent figures of contemporary German poetry, Jan Wagner. His linguistically simple haiku titled teebeutel (tea bag), which has also been translated into Slovenian, shows how inspiring, liberating, and creative German language teaching can be when one dares to include literary texts. Finally, the discussion turns to a canonical author, the giant of German literature, Johann Wolfgang von Goethe. The analysis of his poem Gefunden (The Found Flower) reveals various ways the text can be approached in German lessons: from traditional nature poetry to eco-critical perspectives, and interpretations related to the themes of love and gender discourse at the turn of the 18th century (and beyond). In conclusion, it can be stated that the use of poetry in German as a foreign language teaching is meaningful, not despite the fact but precisely because it confronts students with different, previously unknown, and unusual perspectives on language, society, interpersonal relationships, and aesthetics.